A simple method for isolation of rest of trypsinized stem cells with magnetic beads - Bhatia, Sudhir (Jurnal Teknologi Laboratorium, 2021)
Till now, there is no laboratory in the world, which makes thoughts that there may be still stem cells remaining in the flasks after the trypsin treatment. The user checks the presence of stem cells during trypsinization with the microscope whether the whole population of stem cells has been collected. Magnetic beads are being used around the world to isolate different kinds of cells like CD4, CD8, CD34, and other cells. One of the advantages of magnetic isolation is that they can be used to isolate cells from solutions containing even a low number of targeted cells. We conducted the experiments to see whether all remaining MSC can be obtained from a trypsin-treated flask with magnetic beads isolation. During the magnetic isolation with CD90 specific Magnetic beads, it was found under the microscope that there are huge numbers of cells being attached to beads. The results indicate that there are still a huge number of rest cells in the trypsinized flask but most of the users think that they have isolated all cells, which is not true and they are throwing away valuable stem cells. The magnetic beads can be used to isolate the rest of MSC because for many applications, there is a need of the largest number of stem cells for conducting studies like flow cytometry, molecular testing along with pre-clinical and clinical studies.